NEO-GLS: Innovating School Literacy with Read Aloud and DEAR for Indonesian Students - Putra, Ikhza Mahendra; Dari, Mika Wulan; Wartiningsih, Agus (Universitas Tanjungpura, 2024)
This study examines the innovation of NEO-GLS (New Evolution of School Literacy Movement), Gerakan Literasi Sekolah (GLS) development aimed at improving literacy among Indonesian students. NEO-GLS is an evolution of the previous national literacy program, offering a more structured and interactive approach to addressing 21st-century literacy challenges. In response to data highlighting low literacy rates, NEO-GLS aims to create an inclusive and interactive literacy environment that fosters both academic growth and social engagement. The program integrates two key innovative methods: Read Aloud and Drop Everything and Read (DEAR). These methods are designed to enhance students' reading skills and encourage interest, motivation, and active participation in the learning process. By incorporating enjoyable and engaging reading activities, the program helps develop students